PEOPLE, PUBLIC PARTICIPATION, FORESTS, AND TRAINING - H. Henning, Daniel (วารสารวนศาสตร์ไทย, 2022)
Public participation in forest assessments, planning, and decision-making has become increasingly important in recent years. Forest personnel at various levels should consider it. Concepts and approaches to solicit and incorporate public participation need to be included in in-service training programs. This training would assist personnel in identifying values and making value judgments, and enhance public participation. Too often public participation becomes a farce (and difficult) with agencies fortified with technical data and expert opinions that are not plainly visible. Training in new perspectives and analysis of values and public participation can greatly aid personnel in this vital area. This paper emphasizes various objectives, concepts, and methods of public participation for forestry and training.